Etnomatematika Tradisi Meron di Sukolilo dan Kaitannya dengan Pembelajaran Geometri - Asyrifah Zaini Wahdah; Arghob Khofya Haqiqi; Putri Nur Malasari (Institut Agama Islam Negeri Curup, 2021)
As an effort to assist in improving the quality of education, mathematics is taught to students in formal educational institutions from the basic level of education. However, many students do not like mathematics and consider it the most difficult subject. To address this, teachers can apply ethnomathematics learning to learning activities. One of the cultures that can be used is the meron tradition. The meron tradition is one of the traditions of Islamic ritual ceremonies in Sukolilo which is intended as an event to commemorate the birthday of the Prophet Muhammad. The purpose of this study is to examine the existence of ethnomathematics in the meron tradition in Sukolilo, on the topic of geometry in learning mathematics. This research was conducted using qualitative research with an ethnographic approach. The research data collection techniques about the meron tradition, using interview techniques, and documentation with research instruments include interview guidelines and field notes. Interviews were conducted with five residents of Sukolilo. Data analysis used descriptive qualitative method. The results showed that the concept of ethnomathematics in the meron tradition can be seen in each part of the meron. In the mustaka section there is a wreath in the form of a flat circular shape and in the miniature form of the mosque there is a rectangular shape of a cube and pyramid, the gunungan section has a cone shape, the ancak section has two flat shapes, namely a rectangle and a trapezoid.